Investment Repercussions: Reply - Lachmann, L. M. (Quarterly Journal of Economics, 1949)
Investment Repercussions: A Reply L. M. Lachmann L. M. Lachmann University of the Witwatersrand, South Africa Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 63, Issue 3, August 1949, Pages 432–434, https://doi.org/10.2307/1882265 Published: 01 August 1949